The role of circulating neutrophils in the progression of kidney cancer - I. R. Magdieva; T. V. Abakumova; D. R. Dolgova; O. Y. Gorshkov; T. P. Gening (Успехи молекулярной онкологии)
Introduction. Currently, the question of the role of neutrophils in the progression of kidney cancer remains relevant. Neutrophils are capable of exhibiting protumor properties through the secretion of cytokines, chemokines, and growth factors, which is determined by the expression of genes for these molecules. And the functional heterogeneity of neutrophils is characterized by differences in gene expression patterns.Aim. To assess the role of circulating neutrophils in the progression of kidney cancer.Materials and methods. In circulating neutrophils of patients with verified clear cell kidney cancer at stages I–III according to Tumor, Nodus and Metastasis (TNM) (n = 88) before surgical treatment and conditionally healthy donors (control group) (n = 20), the expression of NGAL genes was determined using quantitative reverse transcription polymerase chain reaction, MMP-13 and VEGF-A.Results. There was an increase in NGAL gene expression in circulating neutrophils (p = 0.05) at the initial stage and a decrease in it at advanced stages of kidney cancer (p = 0.03). High expression of the MMP-13 gene by circulating neutrophils was detected at all stages of kidney cancer relative to control values (at stage I p = 0.005; at stage II p = 0.003; at stage III p = 0.0008). A significant direct correlation was observed between the expression of the NGAL and MMP-13 genes in neutrophils at stage I kidney cancer (r = 0.696; p = 0.003). In the group of patients with kidney cancer, a direct correlation was found between the expression of the NGAL and VEGF-A genes (r = 0.322; p = 0.049). A multivariable Cox regression model for disease-free survival revealed the predictive value of VEGF-A and NGAL genes expression in circulating neutrophils. With an increase in the expression of the VEGF-A and NGAL genes in neutrophils by 1 unit, the risk of metastases increases by 0.80 (0.65–0.99; p = 0.043) and 1.42 (1.01–2.00; p = 0.046) times, respectively. The Kaplan–Meier analysis of disease-free survival in patients with kidney cancer showed the influence of NGAL expression in circulating neutrophils on progression-free time. In the group of patients with high NGAL expression, the median follow-up was 31.7 months, and in the group with low NGAL expression – more than 36 months (log-rank-test; p = 0.017).Conclusion. Thus, the data obtained suggest that circulating neutrophils play a leading role in the progression of kidney cancer. The level of expression of NGAL in circulating neutrophils can be used to predict the relapse-free period in patients with kidney cancer.